The relationship between the quality of nutrition-related weight loss TikTok content and Philippine healthy eating index scores in select UP Diliman undergraduates - Celestial, John William P.; Masinna, Gem Evajones G.; Orígenes, Joshua Miguel T.; Vinuya, Cesar Justin C.; Bayaga, Cecile Leah T. (Quezon City University of the Philippines Diliman, 2025)
TikTok, the world’s fastest-growing social media platform, has rapidly become a primary source of nutrition information for young adults. However, studies suggest that a large proportion of this content may be misleading or inaccurate. This research investigated the relationship between the quality of nutrition-related weight loss TikTok content—evaluated using the DISCERN tool—and the diet quality of 18-to-24-year-old undergraduate students from the University of the Philippines Diliman, measured through the Philippine Healthy Eating Index (PHIL-HEI). Using a cross-sectional, correlational quantitative research design, 67 participants submitted TikTok videos they had recently watched and completed two non-consecutive 24-hour food recalls. These were used to compute individual DISCERN and PHIL-HEI scores. Findings revealed that while participants were exposed to moderately reliable videos (mean DISCERN score: 3.82), there was no statistically significant relationship between video quality and PHIL-HEI scores (ρ = -0.13, p = 0.2982). This suggests that exposure to digital health content does not necessarily translate into healthier eating behaviors. The study highlights that while TikTok may shape nutrition awareness, its isolated influence on actual dietary behavior is limited. Environmental constraints such as low food budgets and limited cooking access, along with personal factors like stress, smoking, and alcohol use, while not directly examined, may have played a substantial role in shaping diet quality than the quality of TikTok videos alone.. These findings underscore the need for a comprehensive health promotion strategy that integrates digital literacy, behavioral motivation, and supportive environments. Future studies should refine participant selection and assess content exposure more holistically to better reflect real-world influences on dietary behavior.
In partial fulfillment for the Degree of Bachelor of Science in Community Nutrition
Thesis
Keywords: Public health; Social media -- Influence; Nutrition policy -- Philippines; TikTok; Nutrition-related content; Weight Loss; PHIL-HEI.